Sanitary Risks Connected to the Consumption of Infusion from Senna rotundifolia L. Contaminated with Lead and Cadmium in Cotonou (Benin). (29th January 2014) - Montcho, S. A.; Koudouvo, K.; Yehouenou, A. P. E.; Guedenon, P.; Koumolou, L.; Sopoh, M. Oke; Dougnon, V.; Gbéassor, Mensavi F.; Creppy, E. E.; Boko, M.; Edorh, A. P.
Abstract : This study carried out an assessment of sanitary risks connected to the consumption of Senna rotundifolia Linn. contaminated with lead and cadmium. This plant was collected and analyzed by atomic absorption spectrophotometry. The results revealed a contamination of plants from markets of Dantokpa, Vossa, and Godomey with heavy metals. Senna from Vossa was higher in cadmium and lead levels (Pb: 2.733 mg/kg ± 0.356 mg/kg; Cd: 0.58 mg/kg ± 0.044 mg/kg) compared to the two other places (Pb: 1.825 mg/kg ± 0.133 mg/kg, Cd: 0.062 mg/kg ± 0.015 mg/kg and Pb: 1.902 mg/kg ± 0.265 mg/kg, Cd: 0.328 mg/kg ± 0.024 mg/kg), respectively, for Dantokpa and Godomey. In terms of risk assessment through the consumption of Senna, the values recorded for lead were nine times higher with children and six times higher with adults than the daily permissive intake (Pb: 3.376 × 10 −2  mg/kg/day for children and 2.105 × 10 −2  mg/kg/day for adults versus 3.6 × 10 −3  mg/kg/day for DPI). With respect to cadmium, there was no significant difference between the recorded values and the DPI (Cd: 1 × 14 10 −3  mg/ kg/day for children and Cd: 0.71 × 10 −3  mg/ kg/day for adults versus Cd: 1 × 10 −3  mg/kg/day for adults). This exposure of the population to lead and cadmium through the consumption of antimalarial healing plants could pose public health problems.